Explaining the Mediatisation Approach - Krotz, Friedrich (Javnost-The Public, 2017)
This article provides an overview of the mediatisation approach, which for the last two decades has gradually become a systematic concept for understanding and theorising the transformation of everyday life, culture and society in the context of the ongoing transformation of media. The article is divided into four sections. The first section addresses the ongoing transformation of media and the emergence of a computer-controlled digital infrastructure for all symbolic operations in a society; some of the new types of media are also presented. In the second section, the development of the mediatisation approach as a reaction to media changes is explained, and the central assumptions and conditions of this approach are discussed. This section also shows why, in addition to actual mediatisation research, historical mediatisation research is also necessary to understand the developments occurring today. The third section clarifies this and discusses how the transformation of media produces a transformation of everyday life, culture and society; this section also presents some results of empirical studies. The fourth and final section provides some preliminary ideas about how to establish a necessary third branch of mediatisation research, which offers a critical view with reference to civil society, besides actual and historical mediatisation research.